Enhancing quality characteristics and controlling gray mold disease caused by Botrytis cinerea in strawberries fruits using various edible abiotic coatings - Areej SAUD JALAL; Ayat M. ALI; Mohamed A. ABOU-ZEID; Shouaa A. ALROBAISH; Enas A. ALMANZALAWI; Tahani M. ALQAHTANI; Diaa ABD EL MONEIM; Marian THABET (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
The study aimed to evaluate the efficiency of chitosan, potassium silicate, and calcium chloride as edible abiotic coatings in controlling the postharvest gray mold disease of strawberries caused by Botrytis cinerea, reducing the use of chemical fungicides and managing fruit decay. Two pure isolates of B. cinerea were extracted from strawberry fruits of cv. ‘Festival’, identified based on morphological features, and their rDNA sequences were sequenced using BLAST and phylogenetic analysis, showing 98.9-100% equivalence. The ITS sequences have been deposited in Gene Bank and assigned accession numbers MT708074 and MT704983. In vitro, all treatments inhibited linear growth of both isolates, with chitosan and potassium silicate were the most effective against the two isolates. In vivo test showed a significant decrease in gray mold incidence and severity. The study revealed that potassium silicate significantly reduced disease incidence in strawberry fruit cultivars ‘Fortuna’ and ‘Festival’ from Qalyubia governorate, while chitosan achieved the greatest reduction in disease severity in samples from Beheira governorate. Both treatments increased the total phenolic and peroxidase activity. The study found that application of potassium silicate and chitosan to strawberry fruit in ‘Fortuna’ and ‘Festival’, resulted in higher sugar and ascorbic acid content, increased fruit firmness, and decreased respiration rate, suggesting that these treatments could potentially reduce postharvest decay and enhance fresh strawberry fruit quality.